Identification of persuasive elements in Islamic knowledge website using Kansei engineering - Nor Aziah Daud; Nurul Izzati Aminudin; Fauziah Redzuan; Noraidah Sahari Ashaari; Zurina Muda (Bulletin of Electrical Engineering and Informatics, 2019)
The global explosions of the internet and direct use by individuals, organizations and Islamic scholars to spread the knowledge and events have witnessed massive growth over the years. The users refuse to use online Islamic websites as references which causes the acceptance rate of the online learning method still low. This paper presents the identifications of persuasive elements in Islamic knowledge website. The objective of this study is to identify the persuasive element using Kansei Engineering (KE) method for online Islamic knowledge website design. Therefore, Kansei words related to online Islamic knowledge were identified. After that, the Kansei words (KWs) were evaluated in order to be used as persuasive elements. Ten specimens of Islamic websites were chosen and evaluated with 30 emotions of KWs. 38 students from one of the public universities accomplished the evaluation experiment. The gathered KWs were then analyzed using multivariate analysis such as Factor Analysis to identify the persuasive elements. Based on Factor Analysis, the finding of this research revealed four main pillars which are credibility-motivated, reliability, Islamic identity and functional. The two additional pillars are updated and belief. The pillars were then compared with the persuasive elements in the previous research. Although there are some limitations and constraint during the conduct of the research, this study also contributes to the design persuasive elements for Islamic website knowledge in the future.